The effectiveness of telemedicine in the prevention of type 2 diabetes mellitus : a systematic review and meta-analysis of interventions - Suhlrie, Laura; Ayyagari, Raga; Mba, Camille; Olsson, Kjell ; 0000-0002-1008-2690; Torres-Aparcana, Harold; James, Steven; Vounzoulaki, Elpida; Ibsen, Daniel B. (Diabetes and Metabolic Syndrome: Clinical Research and Reviews, 2025)
Objective: To evaluate the effectiveness of telemedicine-delivered diet and/or exercise interventions to prevent type 2 diabetes (T2D) in people at risk. Methods: Embase (via Ovid), Medline (via Ovid), Web of Science, CINAHL, Scopus and SciELO were searched from January 2010–December 2020 for intervention studies using a diet and/or exercise intervention delivered through telemedicine for T2D prevention in people at risk. Parallel randomised controlled trials were meta-analysed, and other intervention designs narratively synthesized. Results: We identified 11,645 studies via database searches, of which 226 were full-text screened, and 52 interventions included; 32 were included in the meta-analysis and 20 in the narrative synthesis. Telemedicine interventions reduced body weight (mean difference (MD): −1.66 kg, 95 % confidence interval (CI) −2.48,-0.90, I2 = 81 %, nstudies = 17), body mass index (MD -0.71 kg/m2, 95 % CI -1.06,-0.37, I2 = 70 %, nstudies = 11), waist circumference (MD -2.82 cm, 95 % CI -5.16,-2.35, I2 = 84 %, nstudies = 8) and HbA1c (MD -0.07 %, 95 % CI -0.14,0.00, I2 = 71 %, nstudies = 11). No significant effects were found for other clinical outcomes. The narrative synthesis supported the results. The longest follow-up time was up to 24 months. Conclusions: Our study demonstrates effectiveness for telemedicine-delivered interventions in preventing T2D in people at risk, specifically in people with overweight/obesity.
Publisher Copyright: © 2025 Research Trust of DiabetesIndia (DiabetesIndia) and National Diabetes Obesity and Cholesterol Foundation (N-DOC)